(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses some of the problems of refugees in Kyrgyzstan. Special attention was paid to the situation of ethnic Kyrgyz who fled Tajikistan. There is evidence that ethnic Kyrgyz, who were initially refugees, gradually began to permanently reside in Kyrgyzstan. The Kyrgyz authorities have adopted a number of legislative acts for integration processes. These include the Decree of the President of the Kyrgyz Republic, resolutions and laws of the Housing and Communal Complex, the government program “Kairilman” and others. This is presented as an important work for the reception of refugees. It also contains the results of scientific research on the status, location and number of refugees.